Creation and Implementation of an Outpatient Pathway for Atrial Fibrillation in the Emergency Department Setting: Results of an Expert Panel. (17th April 2018) - Baugh, Christopher W.; Clark, Carol L.; Wilson, Jason W.; Stiell, Ian G.; Kocheril, Abraham G.; Luck, Krista K.; Myers, Troy D.; Pollack, Charles V.; Roumpf, Steven K.; Tomassoni, Gery F.; Williams, James M.; Patel, Brian B.; et al.
Abstract: Atrial fibrillation and flutter (AF) is a common condition among emergency department (ED) patients in the United States. Traditionally, ED care for primary complaints related to AF focus on rate control, and patients are often admitted to an inpatient setting for further care. Inpatient care may include further telemetry monitoring and diagnostic testing, rhythm control, a search for identification of AF etiology, and stroke prophylaxis. However, many patients are eligible for safe and effective outpatient management pathways. They are widely used in Canada and other countries but less widely adopted in the United States. In this project, we convened an expert panel to create a practical framework for the process of creating, implementing, and maintaining an outpatient AF pathway for emergency physicians to assess and treat AF patients, safely reduce hospitalization rates, ensure appropriate stroke prophylaxis, and effectively transition patients to longitudinal outpatient treatment settings from the ED and/or observation unit. To support local pathway creation, the panel also reached agreement on a protocol development plan, a sample pathway, consensus recommendations for pathway components, sample pathway metrics, and a structured literature review framework using a modified Delphi technique by a technical expert panel of emergency medicine, cardiology, and other stakeholder groups.